Linking Tourist Willingness to Pay and Beach Management: A Travel Cost Analysis for Balandra Marine Park, Mexico - Mónica Moreno-Gutiérrez; Víctor Hernández-Trejo; Ramón Valdivia-Alcalá; Judith Juárez-Mancilla; Plácido Roberto Cruz-Chávez; Ulianov Jakes-Cota (Tourism and Hospitality)
Balandra, one of the most popular beaches in La Paz, Baja California Sur, was declared a flora and fauna protection area in 2012, and in 2019, the Mexican government chose it as the best beach in Mexico during the Tianguis Turistico celebrated on that year. Because of this latter distinction, this beach currently faces overcrowding. Formulating effective management policies depends, to a certain extent, on the knowledge of their recreational value and visitor characteristics. Recreational value allows us to know the benefits of the tradeoffs among the ecosystem services and society and exhibit the value of possible damages to marine ecosystems, like the one caused in 2022 by the fire of a tourist boat inside Balandra. Using the individual travel cost method and applying 159 questionnaires to site visitors, the individual willingness to pay to access Balandra Beach was estimated, resulting in USD 11.11/day/visitor. Recreational economic value (REV) for Balandra was estimated using two essential criteria: first, the total visitors registered in 2021, and second, the daily maximum carrying capacity. Welfare recreational loss was also calculated, derived from the site’s two-month closure, using REV as a proxy. Finally, beach management options and possible environmental and economic policy instruments that could be implemented are discussed.